Reconstructing the epidemic history of HIV-1 circulating recombinant forms CRF07_BC and CRF08_BC in East Asia: the relevance of genetic diversity and phylodynamics for vaccine strategies. - Takebe, Y; Liao, H; Hase, S; Uenishi, R; Li, Y; Li, X; Han, X; Shang, H; Kamarulzaman, A; Yamamoto, N; Pybus, O; Tee, K (2010)
HIV-1 CRF07_BC and CRF08_BC are closely related circulating recombinant forms (CRFs) with serious public health consequences in China. The temporal and spatial dynamics of these CRFs were determined by estimating their times of divergence, using phylogenetic and Bayesian coalescent methods. Studies of the timelines of CRF07_BC and CRF08_BC trace the expansion of these strains back their origins to Yunnan province. The present study highlights the relevance of incorporating evolutionary and molecular epidemiological analyses into an in-depth understanding of the genesis of HIV epidemic, providing information for determining regional and global public health policies, including future vaccine strategies.